2020
DOI: 10.1093/mnras/staa570
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric analysis of prompt emission of GRB 160325A: jet with evolving environment of internal shocks

Abstract: GRB 160325A is the only bright burst detected by AstroSat CZT Imager in its primary field of view to date. In this work, we present the spectral and polarimetric analysis of the prompt emission of the burst using AstroSat, Fermi and Niel Gehrels Swift observations. The prompt emission consists of two distinct emission episodes separated by a few seconds of quiescent/ mild activity period. The first emission episode shows a thermal component as well as a low polarisation fraction of PF < 37 % at 1.5 σ confidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 123 publications
(175 reference statements)
1
9
0
Order By: Relevance
“…Finally, we only see signs of an evolving PA inside of single pulses. We do not see any signs of evolving polarization angles outside of individual pulses or in overlapping pulses, such as those reported for example by GAP for GRB 100826A (Yonetoku et al 2011) or by the AstroSat CZT-Imager collaboration for GRB 160821A (which consists of a single emission episode but with several overlapping pulses) and 160325A (Sharma et al 2019a(Sharma et al , 2020.…”
Section: Resultssupporting
confidence: 53%
“…Finally, we only see signs of an evolving PA inside of single pulses. We do not see any signs of evolving polarization angles outside of individual pulses or in overlapping pulses, such as those reported for example by GAP for GRB 100826A (Yonetoku et al 2011) or by the AstroSat CZT-Imager collaboration for GRB 160821A (which consists of a single emission episode but with several overlapping pulses) and 160325A (Sharma et al 2019a(Sharma et al , 2020.…”
Section: Resultssupporting
confidence: 53%
“…The Cadmium Zinc Telluride Imager (CZTI) on board AstroSat reported high polarization for most of the 11 bright GRBs detected in the first year of its operation (Chattopadhyay et al 2019). Detailed spectropolarimetric analysis of some of these bright GRBs revealed time-and energy-dependent variation in polarization happening across the burst duration (Chand et al 2018(Chand et al , 2019Sharma et al 2019Sharma et al , 2020. Most importantly, we note that the detailed study of GRB 160821A showed a ∼90°flip in polarization angle occurring twice within a single broad emission pulse (Sharma et al 2019).…”
Section: Introductionmentioning
confidence: 81%
“…Both the IBIS, GAP, and AstroSAT CZTI collaborations have reported an evolution of the PA over more complex GRBs consisting either of multiple separated pulses (100826A, 160325A) or overlapping pulses (041219A, 160821A) [220,225,226,230]. For both 100826A and 160821A the evolution is reported to be compatible with PA changes of 90 • .…”
Section: Time Resolved Measurementsmentioning
confidence: 76%